2017
DOI: 10.1002/jgt.22182
|View full text |Cite
|
Sign up to set email alerts
|

Dominating induced matchings in graphs containing no long claw

Abstract: An induced matching M in a graph G is dominating if every edge not in M shares exactly one vertex with an edge in M. The dominating induced matching problem (also known as efficient edge domination) asks whether a graph G contains a dominating induced matching. This problem is generally NP‐complete, but polynomial‐time solvable for graphs with some special properties. In particular, it is solvable in polynomial time for claw‐free graphs. In the present article, we provide a polynomial‐time algorithm to solve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…One of the most difficult parts of such proofs is finding good transformations. Actually, one not only wants correct transformations but also simple transformations to simplify the proof and as few as possible to avoid long and repetitive proofs (an example with more than 40 transformations can be seen in [21]). We define the simplicity of a transformation as the number of elements of the graph (vertices and edges) touched by the transformation.…”
Section: Transproofmentioning
confidence: 99%
“…One of the most difficult parts of such proofs is finding good transformations. Actually, one not only wants correct transformations but also simple transformations to simplify the proof and as few as possible to avoid long and repetitive proofs (an example with more than 40 transformations can be seen in [21]). We define the simplicity of a transformation as the number of elements of the graph (vertices and edges) touched by the transformation.…”
Section: Transproofmentioning
confidence: 99%
“…More recently, the corresponding weighted problem has been solved in O(n) time, by Lin, Mizrahi and Szwarcfiter [12]. Moreover, Hertz, Lozin, Ries, Zamaraev and de Werra [9] have shown that the efficient edge domination problem can still be solved in polynomial time for graphs containing no long claws. Finally, for bounded degree graphs, Cardoso, Cerdeira, Delorme and Silva [4] have shown that efficient edge domination problem is NP-complete for r-regular graphs for r ≥ 3.…”
Section: Efficient Edge Dominationmentioning
confidence: 99%
“…The problems consist in determining such dominating sets, of minimum cardinality or minimum total weight of their edges. Most of the known results, so far concerned the efficient edge dominating case (also known as dominating induced matching), for instance see [2,3,4,6,8,9,10,11,12,13,14,15,16,17]. These two types of dominations may lead to problems of a quite different nature.…”
Section: Introductionmentioning
confidence: 99%
“…The following results are known: Theorem 1. DIM is solvable in polynomial time for (i) S 1,1,1 -free graphs [9], (ii) S 1,2,3 -free graphs [12], (iii) S 2,2,2 -free graphs [11], (iv) S 1,2,4 -free graphs [6], (v) S 2,2,3 -free graphs [7], (vi) S 1,1,5 -free graphs [8], (vii) P 7 -free graphs [4] (in this case even in linear time), (viii) P 8 -free graphs [5].…”
mentioning
confidence: 99%
“…In [11], it is conjectured that for every fixed i, j, k, DIM is solvable in polynomial time for S i,j,k -free graphs (actually, an even stronger conjecture is mentioned in [11]); this includes P k -free graphs for k ≥ 9. In this paper we show that DIM can be solved in polynomial time for P 9 -free graphs (generalizing the corresponding results for P 7 -free and for P 8 -free graphs).…”
mentioning
confidence: 99%